Examination of inclusive educational experiences of refugee students in secondary and high schools in Turkey - Kazu, Hilal; Deniz, Emrullah (Whole Schooling Consortium, 2022)
This study aims to determine the views of students with refugee status who have emigrated to Turkey for various reasons and are continuing their education in secondary and high schools about the Turkish education system. A total of 149 students (76 male, 73 female) in two different groups, who were attending grades 5-8 and 9-12 in the 2018-2019 academic year, participated in the study which used descriptive research and the survey model in conjunction with each other. The results showed that although the education staff welcomed refugee students, they could not make academic adaptations to suit the unique characteristics of these students. While it was found that the majority of students (51%) had adapted to school in Turkey, some (30%) were not actively attending school, and some (27%) had difficulty meeting their basic needs. The results regarding communication and cooperation showed that while these students could easily express themselves to their classmates and teachers, around 20% experienced undecidedness. Data obtained directly from refugee students in this study are crucial for developing policies and projects to give them access to education, enable them to adapt, and guide future studies. More studies are needed to monitor whether the inclusive practices used in Turkey and throughout the world indeed meet what is intended.
Keywords: Refugee; refugee student; student views; inclusive education